2013
DOI: 10.1177/0218492312462576
|View full text |Cite
|
Sign up to set email alerts
|

What outcome after the prescription of neoadjuvant chemotherapy in lung cancer?

Abstract: Neoadjuvant chemotherapy offers several potential benefits, but it may delay surgery or eliminate eligibility as a surgical candidate. Rigorous patient selection for this type of multimodal treatment is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Patients with NSCLC in stage IIB/IIIA generally have unfavorable prognosis [ 3 ]. The neoadjuvant chemotherapy (NAC) prior to surgery has been reported to shrink and reduce the primary tumor and distant micro-metastases, thereby reducing the high relapses rates [ 4 ]. In our previous study, platinum-based NAC was demonstrated to significantly increase disease-free survival (DFS) time for patients with stage IIB-IIIA central disease [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with NSCLC in stage IIB/IIIA generally have unfavorable prognosis [ 3 ]. The neoadjuvant chemotherapy (NAC) prior to surgery has been reported to shrink and reduce the primary tumor and distant micro-metastases, thereby reducing the high relapses rates [ 4 ]. In our previous study, platinum-based NAC was demonstrated to significantly increase disease-free survival (DFS) time for patients with stage IIB-IIIA central disease [ 5 ].…”
Section: Introductionmentioning
confidence: 99%